Images of Iceland and Greenland in the Late Seventeenth and First Half of the Eighteenth Century - Ísleifsson, Sumarliði R. (1700-tal: Nordic Journal for Eighteenth-Century Studies, 2015)
This article considers external images of Iceland and Greenland from the latter part of the seventeenth century and the first half of the eighteenth century in terms of their perceived ‘otherness’ during that period. The main methodologies used are approaches derived from imagology, or image studies, and postcolonial studies. The principal sources used are published writings by Western European authors, mostly from Britain and Germany. In essence, the most common discourse on Iceland and Greenland during the period in question reflects that of other marginal lands and territories most under Western European influence. While images of these two countries did have their own characteristics because of their ‘islandness’, they were distinguished first and foremost as being situated in the high north. We can call the qualities that were attributed to them borealism, a kind of orientalism or tropicality of the high north. One of the dominant themes in the otherness of these two northern islands is what might be called ‘primitive utopia’. The representation of Iceland and Greenland as paradise islands, even treasure islands, was also familiar. Negative and dystopian ideas were also common, in fact much more so for most of the period. By these accounts, the countries were described as uninhabitable because of the prevailing cold and wildness, and their crude barbarian inhabitants were depicted as being hardly distinguishable from animals. The same kind of dualism found in the narratives of the European Other in general was clearly an important factor in the process of the identity formation of these two islands.